Архелај и престолот – Archelaus and the throne - Саракински, Војислав (Филозофски факултет, Скопје, 2020)
The philosopher Plato claims that the Macedonian king Archelaus was the illegitimate son of Perdiccas II and a slave, and that he allegedly killed all the legitimate heirs to the throne and used force to seize the royal power in Macedonia. Though this story was well known in ancient times, modern scholars dispute it, either fully or partially; nevertheless, all attempts to prove that it is unfounded are based on assumptions and a conjecture of circumstantial arguments. The reanalysis of our sources, as well as a comparison with suitable examples concerning the succession of royal power in Macedon point out that succession issues in Aegae were not, however, completely clear-cut; that the silence of Thucydides concerning the transfer of power, until he had introduced Archelaus as king, though not decisive, may nevertheless be indicative; that the position of Archelaus in terms of succession was complicated, regardless of whether he was a legitimate son; and finally, that, if nothing else, the story of Plato deserves much greater scrutiny and should by no means be disregarded due to academic inertia, as is usually the case.
Keywords: Archelaus, Alcetas, Plato, Succession, Macedonia, throne